Evaluasi Kinerja Penjualan dan Efisiensi Iklan Kampanye GMV Max pada TikTok Shop Garage Fortress - Rachman Hidayat; Jeffri Prayitno Bangkit Saputra; Luzi Dwi Oktaviana (Institut Teknologi Garut, 2026)
The growth of social commerce has driven changes in digital marketing strategies that are increasingly data-driven and automated on e-commerce platforms. One of the features utilized in TikTok Shop is GMV Max, an automated campaign system designed to optimize sales performance through platform-based advertising management. This study aims to describe and evaluate the sales performance of TikTok Shop Garage Fortress under the GMV Max campaign using a descriptive quantitative approach based on secondary data obtained from campaign reports covering the period from October 9, 2025, to April 6, 2026. The analysis focuses on GMV, number of orders, advertising costs, ROAS, and conversion rate indicators without examining causal relationships among variables. The results show that the GMV Max campaign generated a total GMV of IDR 25,608,081 with 772 orders, advertising expenditure of IDR 2,324,547, a weighted ROAS of 11.02×, and a conversion rate of 6.15 percent. The GLASSWOOL product campaign contributed the largest share of sales value and number of orders. Based on advertising content type, video advertisements demonstrated higher performance in terms of GMV and ROAS, while product cards achieved a higher conversion rate. Overall, the findings indicate that the GMV Max campaign within the research dataset produced a positive ROAS and measurable conversion rate, although the interpretation of the results should still consider data quality and potential attribution anomalies within the TikTok Shop platform.